2019
DOI: 10.5194/acp-2019-1100
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Characterization of the light absorbing properties, chromophores composition and sources of brown carbon aerosol in Xi'an, Northwest China

Abstract: <p><strong>Abstract.</strong> The impact of brown carbon aerosol (BrC) on the Earth's radiative forcing balance has been widely recognized but remains uncertain, mainly because the relationships among BrC sources, chromophores, and optical properties of aerosol are poorly understood. In this work, the light absorption properties and chromophore composition of BrC were investigated for samples collected in Xi'an, Northwest China from 2015 to 2016. Both absorption &a… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…Previous numerous studies have shown that combustion of fossil fuel and biomass burning (BB) were major sources of BC aerosols ( Zhao et al, 2012 ; Cheng et al, 2013 ; Zhang et al, 2017 ; Ni et al, 2018 ). Although the origins of BrC are not well characterized, biomass burning, coal combustion and vehicle emissions along with biogenic release of fungi, plant debris and humic matter are considered important sources of primary BrC ( Andreae and Crutzen, 1997 ; Rizo et al, 2011 , 2013 ; Yan et al, 2017 ; Zhang et al, 2017 ; Yuan et al, 2019 ). Secondary BrC can be produced by multi-phase reactions between gas-phase, particles and in-cloud processes ( Harrison et al, 2005 ; Nozière et al, 2007 ; De Hann et al, 2009 ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous numerous studies have shown that combustion of fossil fuel and biomass burning (BB) were major sources of BC aerosols ( Zhao et al, 2012 ; Cheng et al, 2013 ; Zhang et al, 2017 ; Ni et al, 2018 ). Although the origins of BrC are not well characterized, biomass burning, coal combustion and vehicle emissions along with biogenic release of fungi, plant debris and humic matter are considered important sources of primary BrC ( Andreae and Crutzen, 1997 ; Rizo et al, 2011 , 2013 ; Yan et al, 2017 ; Zhang et al, 2017 ; Yuan et al, 2019 ). Secondary BrC can be produced by multi-phase reactions between gas-phase, particles and in-cloud processes ( Harrison et al, 2005 ; Nozière et al, 2007 ; De Hann et al, 2009 ).…”
Section: Introductionmentioning
confidence: 99%